Theoretical Investigation of Starved Porous Journal Bearings Anisotropic Permeability with - Abass, Basim A.; Abd-Alsheed, Liqaa H. (Nahrain University College of Engineering Journal, 2009)
The present study is a theoretical analysis to evaluate the static characteristics of oil filled porous journal bearing with non uniform permeability using an improved boundary condition. The analysis was carried out for a porous bearing with a permeability of the bearing ends is lower than that of the middle. The circumferential boundary condition for the oil film pressure is obtained by an integral momentum equation to the oil film region in the bearing clearance. It was found that a porous bearing with anisotropic permeability enhances the load carrying capacity of the bearing, also the bearing oil film is extended along specified extent.